Pembuatan Pupuk Organik Cair (POC) untuk Pertanian Berkelanjutan di Desa Tuah Indrapura, Kabupaten Siak - Hamdani, Rahmad (Jurnal Pengabdian UntukMu NegeRI, 2026)
Tuah Indrapura Village, Bunga Raya District, Siak Regency, is an area where most of the community work as farmers and gardeners. Chemical fertilizers continue to play a significant role in this village's agriculture, despite the fact that they pose long-term environmental risks by reducing soil fertility. Contrarily, there are plenty of underutilized organic resources in Tuah Indrapura Village, including things like food scraps and other forms of household garbage. Thus, in an attempt to promote sustainable agriculture, initiatives are being implemented to help with the production of Liquid Organic Fertilizer (POC) and to provide training in this area. The goal of this event is to teach people how to make POC using sustainable, locally sourced organic materials in an eco-conscious way. Methods for implementation include counseling and creating POC via hands-on practice. Participation in the activity was high, and participants showed a lot of interest in learning how to make and use liquid organic fertilizer on their own. The goal of this project is to promote sustainable agriculture in Tuah Indrapura Village while simultaneously decreasing the use of chemical fertilizers and increasing soil fertility.